Enhanced properties of a positive-charged nanofiltration membrane containing quaternarized chitosan through second interfacial polymerization for the removal of salts and pharmaceuticals - Bai, Xinhui (Water science and technology : a journal of the International Association on Water Pollution Research, 2024)
© 2024 The Authors This is an Open Access article distributed under the terms of the Creative Commons Attribution Licence (CC BY-NC-ND 4.0), which permits copying and redistribution for non-commercial purposes with no derivatives, provided the original work is properly cited (http://creativecommons.org/licenses/by-nc-nd/4.0/).